Analisis Kegunaan Sistem Informasi Akademik Politeknik Negeri Sriwijaya Menggunakan Metode UTAUT - Fitrianto Puja Kesuma; Krisna Nata Wijaya; Surahmat Surahmat (Pusat Riset dan Inovasi Nasional, 2023)
This study is an analysis of the use of Academic Information Systems (SISAK) at the State Polytechnic of Sriwijaya using the UTAUT (Unified Theory of Acceptance and Use of Technology) model. The research method adopts UTAUT, and the dissemination of questionnaires is done through proportionate stratified random sampling. From the analysis carried out, it was found that the performance perspective variable did not have a significant influence on the intensity of behavior in the use of the Academic Information System, and the expected expectations did not affect the intensities of behavior in using the Polytechnic Academical Information System of the State of Sriwijaya (SISAK).